PENGARUH FAKTOR FUNDAMENTAL MAKRO EKONOMI TERHADAP INDEKS LQ45 (PERIODE 2009 â 2013) - Ayuningrum, Imang Indah; Wahidahwati, Wahidahwati (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to analyze the influence of macroeconomic fundamental factor to the LQ45 index in IDX. Independent variables which is used in this research is the interest level BI rates, world gold price, crude oil price, the Unites States Dollar exchange rates (USD), the Nikkei 225 index and Straits Times index. The population is LQ45 index in IDX. The determination of sample is carried out by using purposive sampling; sample of this research is the LQ45 index data which is limited on the closure of the end of the month during the period from January 2009 to December 2013. The multiple linear regressions analysis, classic assumption test, goodness of fit/F-test, determination coefficient test (R2) and hypothesis test(t-test) are used as the analysis method. This research uses the monthly data from 2009 to 2013 for each research variable. The result of the research shows that (1) the interest level of BI rates have negative influence to the LQ45 index; (2) world gold price have positive influence to the LQ45 index, (3)crude oil price do not have any significant influence to the LQ45 index; (4) the United States dollar exchange rates (USD) do not have any significant influence to the LQ45 index; (5) Nikkei 225 index have positive influence to the LQ45 index and (6) Straits Times index have positive influence to the LQ45 index. The adjusted R square value is 94.4%. It means that 94.4% of the movement of LQ45 index can be predicted from the movement of these six independent variables. Keywords: LQ45 Index, Macroeconomic, Multiple Regressions Analysis